Assessing spatial variability in El Niño–Southern Oscillation event detection skill using coral geochemistry. (25th January 2013) - Hereid, Kelly A.; Quinn, Terrence M.; Okumura, Yuko M.
Abstract : [1] The El Niño–Southern Oscillation (ENSO) drives interannual climate variability, but evidence of its preinstrumental expression is limited to proxy data and model inference. We develop a skill assessment technique using instrumental records of sea surface temperature (SST) and sea surface salinity (SSS) and apply it to a suite of 23 coral δ 18 O records, a common ENSO proxy. We compare coral proxy skill with pseudoproxy records constructed from instrumental data to establish the expected proxy response to ENSO events and constrain proxy sensitivity. The central Pacific has a balanced response toward ENSO events, the Western Pacific Warm Pool favors El Niño expression, and the South Pacific Convergence Zone preferentially records La Niña events. However, all three regions display high sensitivity to ENSO variability, presenting promising targets for future coral paleoclimate reconstructions. Eastern Pacific coral records display surprisingly low ENSO sensitivity despite the presence of large ENSO‐related SST anomalies, suggesting nonclimatic influences. Comparisons between the pseudoproxy and coral skill ratings provide a test to highlight where these nonclimatic impacts that may affect coral record skill. Networks of proxy data skill ratings may better delineate the spatial structure of the SST and SSS response to ENSO variability, a feature of the climate system that is currently poorly reproduced in climate models. Key Points: Pseudoproxy forward model sets proper expectation for coral proxy performance High skill ENSO coral records are located in central/western tropical Pacific El Nino and La Nina events are not recorded with equal skill at all locations